2022
DOI: 10.3389/fendo.2022.1043894
|View full text |Cite
|
Sign up to set email alerts
|

The levels of BMI and patterns of obesity and overweight during the COVID-19 pandemic: Experience from the Iran STEPs 2021 survey

Abstract: BackgroundObesity and its increasing burden have become an urgent health problem all over the world. Benefiting from a national representative sample, the present study aimed to estimate the distribution of body mass index (BMI) levels and its association with metabolic and lifestyle risk factors in an Iranian adult population by sex, age, and geographical distribution.MethodsThis study involves a national survey of noncommunicable disease risk factor surveillance (STEPs) in Iran. Through systematic random sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The identification of modifiable risk factors that contribute to dyslipidemia emphasizes the need for comprehensive lifestyle interventions. The study results highlight the urgent need to modify the overweight/obesity trend as the condition with the highest association with dyslipidemia and 63% prevalence in the over 18 years-old Iranian population 24 . There are effective and cost-efficient interventions recommended by WHO for the prevention and control of NCDs and modifying dietary risk factors of obesity and dyslipidemia.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The identification of modifiable risk factors that contribute to dyslipidemia emphasizes the need for comprehensive lifestyle interventions. The study results highlight the urgent need to modify the overweight/obesity trend as the condition with the highest association with dyslipidemia and 63% prevalence in the over 18 years-old Iranian population 24 . There are effective and cost-efficient interventions recommended by WHO for the prevention and control of NCDs and modifying dietary risk factors of obesity and dyslipidemia.…”
Section: Discussionmentioning
confidence: 87%
“…Inappropriate physical activity was reported in 51.3% of the Iranian adult population 23 . Obesity also has considerably increased in recent decades, and STEPs 2021 reported overweight/obesity in 63% of the adult population 24 . This study showed obese persons are 2.8 times more at risk for dyslipidemia than normal-weight adults.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mentioned study found a geographical pattern at the subnational level of Iran, where the level of BMI increased among the population from the southeastern to the northwestern regions ( 30 ). Furthermore, according to the recently published results of Iran STEPS Survey 2021, the national prevalence of normal weight, obesity, and overweight/obesity in Iranian adults was estimated at about 33.61, 24.96, and 63.02%, respectively ( 31 , 32 ). The recent results from NASBOD on obesity showed that, from 1990 to 2016 the mean BMI, and the age-standardized prevalence of overweight has increased ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently with this finding, Lancaster [34] found an association between living with a spouse or partner and overweight/obesity in both men and women but with a stronger association for women. Another study [35] showed that the nevermarried population had the lowest prevalence of overweight and obesity when compared to those married, divorced, and widowed. Thus, the association of the marital status with overweight/obesity can be explained mainly by the increase in moments that encourage the regular consumption of meals, in addition to larger portions, resulting in greater energy intake, as well as a decrease in physical activity and a decrease in the desire to maintain bodyweight to attract a partner [36].…”
Section: Discussionmentioning
confidence: 99%